Kemudahan dalam Pendirian Rumah Ibadat Merupakan sebuah Keniscayaan - Sulistiyono, Obed Meiria (JURNAL ILMIAH GEMA PERENCANA, 2023)
This policy paper aims to obtain policy recommendations regarding the problem of establishing places of worship that are experiencing obstacles in the implementation process in the community. Regulations regarding the establishment of places of worship, namely Joint Regulations of the Minister of Religion and the Minister of Home Affairs Number 9 and Number 8 of 2006, actually become an obstacle due to conditions that are difficult to fulfill, especially for adherents of certain religions and beliefs. Embracing a religion or belief and worshiping in accordance with that religion or belief are human rights that must be protected by the state. This paper uses qualitative research methods by collecting data through interviews, observation, and documentation studies. The results of the study show that there are regulations that hinder the establishment of places of worship. Existing regulations cannot protect and facilitate the establishment of places of worship. Narrow religious understanding results in the absence of religious freedom in the process of establishing places of worship. There is a discriminatory attitude towards certain religions. There is still an understanding that adherents of certain religious minorities cannot build houses of worship in areas where adherents of the majority religion live. Therefore, a policy is needed that can make it easier and protect adherents of religions or beliefs from being able to build houses of worship in accordance with the teachings of their religion and beliefs.